Situación Actual de los Seguros de D&O - Villarreal, Alberto Muñoz (Revista Amagis Jurídica, 2023)
In this article, the author sets out the main characteristics of directors' and officers' liability insurance (D&O insurance in Anglo-Saxon terminology), analyses the current situation of this type of insurance in several European countries and ends by analysing the impact that the health pandemic we are suffering is having on this type of liability and its insurance.